An Acid-Sensitive Bone Targeting Delivery System Carrying Acacetin Prevents Osteoporosis in Ovariectomized Mice - Xiaochen Sun; Chenyu Song; Chenxi Zhang; Chunlei Xing; Juan Lv; Huihui Bian; Nanning Lv; Dagui Chen; Xin Dong; Mingming Liu; Li Su (MDPI AG, 2022)
One effective treatment for postmenopausal osteoporosis is to inhibit osteoclasts and subsequent bone resorption. In our study, we demonstrated that acacetin, a flavone with potential therapeutic effects in infections, cancers, and several metabolic disorders, inhibited osteoclast differentiation and bone resorption in vitro. For improving the efficacy of acacetin in vivo, we developed an acid-sensitive bone-targeting delivery system composed of an acid-sensitive linker (N-ε-maleimidocaproic acid hydrazide, EMCH) for ensuring an effective release of acacetin at the site of action and a hydrophilic aspartic acid hexapeptide ((Asp)6, D6) as the effective bone targeting agent. Our results revealed that Acacetin-EMCH-D6 specifically bound to the bone surface once administrated in vivo, prolonged the retention time in bone and released acacetin at the osteoclastic bone resorption sites where the acidity is higher. We further demonstrated that, in ovariectomy-induced osteoporosis mice, treatment with Acacetin-EMCH-D6 inhibited osteoclast formation and increased trabecular bone mass. On the contrary, neither acacetin nor EMCH-D6 with the same dosage alone showed significant anti-osteoporosis effects in vivo. Mechanistically, targeted delivery of acacetin to the bone resorption sites by Acacetin-EMCH-D6 inhibited autophagy through activating PI3K/AKT/mTOR pathway in osteoclasts, while the activation of autophagy by rapamycin partially reversed the inhibitory effects of acacetin in vitro and in vivo. In summary, our study, for the first time, showed that the acid-sensitive bone-targeting delivery system carrying acacetin was effective for the treatment of postmenopausal osteoporosis. Thus, targeted delivery of acacetin using Acacetin-EMCH-D6 to bone resorption sites is a promising therapy for osteoporosis.